Discovery of novel cold-induced CISP genes encoding small RNA-binding proteins related to cold adaptation in barley. (July 2017) - Ying, Mengchao; Kidou, Shin-ichiro
Highlights: Novel cold-induced barley CISP genes encode small basic proteins. CISP1 homologs were widely distributed in cold-tolerant plants. The expression of barley CISP genes was markedly increased in roots exposed to cold conditions. The CISP1 transcripts were localized in the root tip and lateral root primordium. RNA binding assay suggest CISP proteins are RNA chaperones maintaining root primordium under cold conditions. Abstract: To adapt to cold conditions, barley plants rely on specific mechanisms, which have not been fully understood. In this study, we characterized a novel barley cold-induced gene identified using a PCR-based high coverage gene expression profiling method. The identified gene encodes a small protein that we named CISP1 ( C old-i nducedS mallP rotein 1 ). Homology searches of sequence databases revealed that CISP1 homologs ( CISP2 and CISP3 ) exist in barley genome. Further database analyses showed that the CISP1 homologs were widely distributed in cold-tolerant plants such as wheat and rye. Quantitative reverse transcription PCR analyses indicated that the expression of barley CISP genes was markedly increased in roots exposed to cold conditions. In situ hybridization analyses showed that the CISP1 transcripts were localized in the root tip and lateral root primordium. We also demonstrated that the CISP1 protein bound to RNA. Taken together, these findings indicate that CISP1 and its homologs encoding small RNA-binding proteins may serve as RNA chaperones playing a vital role in the cold adaptation of barley root. This is the first report describing the likely close relationship between root-specific genes and the cold adaptation process, as well as the potential function of the identified genes.